Multi-Source Assessment - A Total Quality Management Driven Performance Appraisal System: The Issue of Fairness (Malaysian Management Journal, 2004)
Performance Management and Total Quality Management are important factors of organizational life, it helps organizations to identify and manage the performance of highs achievers, as well as identify low and non-performers for intervention and development. Total Quality Management takes a system - oriented perspective in managing individuals and group performance and must be compatible with continuous improvement efforts and customer-based strategies. The TQM driven Multi-source Assessment provides an alternative to traditional supervisor only appraisal process. This study was under- taken to determine whether Total Quality Management (TQM) based multi-source assessment (MSA) appraisal is perceived as fairer than traditional supervisor only appraisal system. The study was con- ducted using multi-group experimental design in a field setting. The perceived fairness of the performance assessment system was tested using the combined pretest posttest data of the experimental and control group. The t-test results indicated that changes in agreement scores from pretest to posttest result were significant and respondents perceived the TQM driven MSA process to be fairer The results and discussion of the study show that the MSA process depicts a paradigm shift, not only to management process, but how employees see their changing roles in total quality management driven organization.